Analysis of the Features of Multifactorial Operations and Complex Technological Processes in the Processing of High-Precision Parts - Gafarzada , H.V. (Herald of Azerbaijan Engineering Academy, 2021)
The main features of multifactor operations and complex technological processes used in the processing of high-precision parts of machines and equipment were discussed in the article. The application issues of probability theory and mathematical statistics methods in their modeling, optimization and control are considered.